2022
DOI: 10.1002/adma.202106572
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum Carbide Electrocatalyst In Situ Embedded in Porous Nitrogen‐Rich Carbon Nanotubes Promotes Rapid Kinetics in Sodium‐Metal–Sulfur Batteries

Abstract: abundance of sulfur. The lower cost and greater availability of sodium as compared to lithium precursors is spurring the incremental focus on Na-S batteries. The traditional high temperature Na-S batteries operating at 300-350 °C comprise the molten electrodes and the solid inorganic β-alumina electrolyte. This mature design is known to have safety issues and a relatively low theoretical energy 760 W h kg −1 (2Na + 3S → Na 2 S 3 ). [2] Instead, there is a strong incentive to develop room-temperature (RT) Na-S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 103 publications
2
30
0
Order By: Relevance
“…Room-temperature sodium–sulfur (Na–S) batteries are arousing tremendous interest owing to their high theoretical energy density (1274 Wh kg –1 ) and merits of low cost, resource abundance, and environmental friendliness. Their practical application yet faces the following fundamental challenges: (1) the low electrical conductivity of both the sulfur cathode and its discharge products, sluggish reaction kinetics, and the notorious shuttling effect of sodium polysulfides (NaPS) and (2) uncontrollable dendrite formation of the Na metal anode. To address these issues, polar nanostructured materials including metal nanoparticles, sulfides, oxides, nitrides, and carbide-modified hosts consisting of well-designed active centers have been proven to effectively bind polar NaPS and can be used as electrocatalysts to accelerate the conversion of NaPS to Na 2 S. However, the low-density catalytic active sites and high gravimetric density of bulk metal-containing species would counteract the superiority of the high energy density of Na–S batteries. On the other hand, in Na metal anodes, lightweight porous carbon materials have turned out to be promising host materials for suppressing the Na dendrite formation due to their excellent electrical conductivity and chemical stability. Unfortunately, most carbon skeletons are generally Na-phobic, which requires controlled doping chemistry in a heteroatom-containing carbon matrix to achieve a low energy barrier for Na nucleation and stable Na deposition. , Therefore, it is of great significance to develop a synergistic strategy that can simultaneously regulate both cationic and anionic migration behavior for high-energy-density Na–S battery systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Room-temperature sodium–sulfur (Na–S) batteries are arousing tremendous interest owing to their high theoretical energy density (1274 Wh kg –1 ) and merits of low cost, resource abundance, and environmental friendliness. Their practical application yet faces the following fundamental challenges: (1) the low electrical conductivity of both the sulfur cathode and its discharge products, sluggish reaction kinetics, and the notorious shuttling effect of sodium polysulfides (NaPS) and (2) uncontrollable dendrite formation of the Na metal anode. To address these issues, polar nanostructured materials including metal nanoparticles, sulfides, oxides, nitrides, and carbide-modified hosts consisting of well-designed active centers have been proven to effectively bind polar NaPS and can be used as electrocatalysts to accelerate the conversion of NaPS to Na 2 S. However, the low-density catalytic active sites and high gravimetric density of bulk metal-containing species would counteract the superiority of the high energy density of Na–S batteries. On the other hand, in Na metal anodes, lightweight porous carbon materials have turned out to be promising host materials for suppressing the Na dendrite formation due to their excellent electrical conductivity and chemical stability. Unfortunately, most carbon skeletons are generally Na-phobic, which requires controlled doping chemistry in a heteroatom-containing carbon matrix to achieve a low energy barrier for Na nucleation and stable Na deposition. , Therefore, it is of great significance to develop a synergistic strategy that can simultaneously regulate both cationic and anionic migration behavior for high-energy-density Na–S battery systems.…”
Section: Introductionmentioning
confidence: 99%
“…1−5 Their practical application yet faces the following fundamental challenges: (1) the low electrical conductivity of both the sulfur cathode and its discharge products, sluggish reaction kinetics, and the notorious shuttling effect of sodium polysulfides (NaPS) and (2) uncontrollable dendrite formation of the Na metal anode. 6−9 To address these issues, polar nanostructured materials including metal nanoparticles, 10 sulfides, 11 oxides, 12 nitrides, 13 and carbide 14 -modified hosts consisting of well-designed active centers have been proven to effectively bind polar NaPS and can be used as electrocatalysts to accelerate the conversion of NaPS to Na 2 S. 15−17 However, the low-density catalytic active sites and high gravimetric density of bulk metal-containing species would counteract the superiority of the high energy density of Na−S batteries. On the other hand, in Na metal anodes, lightweight porous carbon materials have turned out to be promising host materials for suppressing the Na dendrite formation due to their excellent electrical conductivity and chemical stability.…”
Section: Introductionmentioning
confidence: 99%
“…22 Such a case has been widely discovered in other studies of S cathode materials for Na-ion storage. 23,24…”
Section: Resultsmentioning
confidence: 99%
“…22 Such a case has been widely discovered in other studies of S cathode materials for Na-ion storage. 23,24 Raman spectroscopy was utilized to further analyze the micro/nanostructures of the samples. For three samples (MnO-C, MnO@NACM, and NACM), two stable and identical characteristic peaks signify the D band (disordered structure) and G bands (graphitized structure) of carbons, respectively, as illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[192][193][194] Remarkably, Hao et al reported a composite cathode with a high sulfur loading of 12.7 mg cm −2 (64 wt.%) and achieved stable cycling for more than 150 cycles. [195] According to the facts, in order to promote the sulfur loads from below 2 mg cm -2 to above 6 mg cm -2 , the focus for RT-Na/S system should be set on the "teamwork" perspective that integrates the abilities of both cathode, anode, electrolyte, separator, and binder rather than developing industrial technology alone.…”
Section: Practical Parametersmentioning
confidence: 99%